The uracil-DNA glycosylase UNG protects the fitness of normal and cancer B cells expressing AID. (27th August 2020) - Safavi, Shiva; Larouche, Ariane; Zahn, Astrid; Patenaude, Anne-Marie; Domanska, Diana; Dionne, Kiersten; Rognes, Torbjørn; Dingler, Felix; Kang, Seong-Kwi; Liu, Yan; Johnson, Nathalie; Hébert, Josée; et al.
Abstract: In B lymphocytes, the uracil N-glycosylase (UNG) excises genomic uracils made by activation-induced deaminase (AID), thus underpinning antibody gene diversification and oncogenic chromosomal translocations, but also initiating faithful DNA repair. Ung −/− mice develop B-cell lymphoma (BCL). However, since UNG has anti- and pro-oncogenic activities, its tumor suppressor relevance is unclear. Moreover, how the constant DNA damage and repair caused by the AID and UNG interplay affects B-cell fitness and thereby the dynamics of cell populations in vivo is unknown. Here, we show that UNG specifically protects the fitness of germinal center B cells, which express AID, and not of any other B-cell subset, coincident with AID-induced telomere damage activating p53-dependent checkpoints. Consistent with AID expression being detrimental in UNG-deficient B cells, Ung −/− mice develop BCL originating from activated B cells but lose AID expression in the established tumor. Accordingly, we find that UNG is rarely lost in human BCL. The fitness preservation activity of UNG contingent to AID expression was confirmed in a B-cell leukemia model. Hence, UNG, typically considered a tumor suppressor, acquires tumor-enabling activity in cancer cell populations that express AID by protecting cell fitness. Graphical Abstract: